Challenges and Advantages of AI into English Language Learning and Teaching (Grammar, Vocabulary, Writing): a Case Study based on ChatGPT - Dubrova, O. V.; Saliuk, B. A.; Moroz, A. A. (НДУ ім. М. Гоголя, 2026)
Relevance of the study. The rapid digital transformation of education, accelerated by the COVID-19 pandemic and the ongoing full-scale war in Ukraine, has intensified the need to integrate AI-based technologies into language teaching. Despite the widespread adoption of ChatGPT globally, empirical research on its pedagogical application in the Ukrainian educational context with its distinct cultural, linguistic, and institutional characteristics remains critically scarce, representing a significant gap in the field. Main objective of the study. This paper aims to analyse the pedagogical potential, practical scenarios, advantages, and challenges of integrating ChatGPT into English language teaching and learning, with a particular focus on grammar, vocabulary, and writing skills development, as well as to provide theoretically grounded and practically tested recommendations for English language teachers operating in Ukrainian educational settings. Methodology. The study employs a theoretical-analytical approach combining a systematic review of international scholarly literature published between 1998 and 2023, critical comparative analysis of empirical studies, and case-study methodology. Drawing on constructivist theory (Vygotsky’s zone of proximal development), Bloom’s research on individualised instruction, communicative language teaching principles, and CALL scholarship, the authors develop and evaluate multiple pedagogically grounded scenarios for ChatGPT integration. The analysis incorporates both quantitative findings from meta analyses and qualitative insights from experimental studies conducted across diverse educational contexts. Results, findings and conclusions. The study identifies four core scenarios for effective ChatGPT integration: developing writing skills through iterative AI-assisted feedback; practising communication in low-anxiety simulated environments; acquiring grammar and vocabulary through active, context-based learning; and supporting autonomous exam preparation aligned with IELTS/TOEFL standards. The key advantages identified include personalised 24/7 learning support, reduced foreign language anxiety, immediate formative feedback, increased learner motivation grounded in self-determination theory, and teachers’ ability to automate routine tasks and focus on creative mentoring. Simultaneously, the study identifies critical challenges: the risk of academic dishonesty (AI-generated texts are extremely difficult to distinguish from student writing), learner over reliance undermining autonomous skill development, ChatGPT’s inability to capture cultural nuances and idiomatic expressions, unresolved data privacy concerns, and the lack of institutional guidelines and teacher training frameworks for AI integration. Significance. The findings contribute to filling a documented gap in AI-in-education research concerning Eastern European contexts. The study offers concrete prompt templates, assessment strategies, and methodological recommendations directly applicable by English language teachers at various proficiency levels. It also outlines an agenda for future empirical longitudinal research examining the long-term impact of ChatGPT on learners’ language proficiency, autonomy, and motivation across different CEFR levels, and calls for evidence-based educational policy on the ethical and equitable use of AI in language education.
Keywords: artificial intelligence, ChatGPT, English language teaching, communicative approach, digital technologies, distance learning